2022
DOI: 10.1155/2022/4954457
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis Analysis and Validation of Fatty Acid Metabolism-Related lncRNAs and Tumor Immune Microenvironment in Cervical Cancer

Abstract: Cervical cancer (CC) is the third most common carcinoma and the fourth leading cause of cancer-associated mortality in women. The deregulation of fatty acid metabolism plays a crucial role in the progression of various tumors. This study is aimed at exploring the prognostic values of fatty acid metabolism- (FAM-) related long noncoding RNAs (lncRNAs) in CC. FAM-related differentially expressed genes (DEGs) and lncRNAs were screened in CC specimens based on TCGA datasets. Univariate analysis was carried out on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…LINC00683 is another intriguing therapeutic target for CESC patients. Based on the available literature we found that AP001528.1, AC119427.1, AC124045.1, PTPRD-AS1, and KIAA0087 could be promising biomarkers for a variety of cancers 53 , 54 , 55 , 56 .…”
Section: Discussionmentioning
confidence: 99%
“…LINC00683 is another intriguing therapeutic target for CESC patients. Based on the available literature we found that AP001528.1, AC119427.1, AC124045.1, PTPRD-AS1, and KIAA0087 could be promising biomarkers for a variety of cancers 53 , 54 , 55 , 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Although some lncRNAs are well characterized functionally, the vast majority of such molecules remain functionally uncharacterized. According to different functional modules, lncRNAs can be finely classified into immune-related lncRNAs ( Ye, Chen & Lu, 2021 ; Zheng et al, 2020 ), ferroptosis-related lncRNAs ( Jiang et al, 2022 ; Li et al, 2022 ), metabolism-related lncRNAs ( Lang, Huang & Cui, 2022 ; Lu et al, 2022 ), etc . Further, we speculated that super-enhancer-associated lncRNAs might be involved in this regulatory mechanism and were significantly regulated by enhancers, especially super-enhancers (SEs) ( Bian et al, 2021 ; Peng et al, 2022 ; Wang et al, 2020 ; Yan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had demonstrated that lncRNA MIR100HG was identified as an oncogene in various cancers, including breast cancer (Chen et al, 2020), hepatocellular carcinoma (HCC) (Li et al, 2021), gastric Frontiers in Genetics frontiersin.org cancer (Li J. et al, 2019;Li et al, 2020), and colorectal cancer (Li W. et al, 2019). However, studies in MIR100HG also proved that it could exert tumor suppressive effects in papillary-thyroid carcinoma (Yang et al, 2021;Park and Lee, 2022) and cervical cancer (Lang et al, 2022;Lin et al, 2022). Furthermore, there are opposing results about the role of lncRNA MIR100HG in bladder cancer (BC).…”
Section: Discussionmentioning
confidence: 99%